Effects of Spilling and Plunging Type Breaking Waves Acting on Large Monopile Offshore Wind Turbines - Tang, Ye; Shi, Wei; Ning, Dezhi; You, Jikun; Michailides, Constantine (Frontiers in Marine Science, 2020)
In the present paper, the computational fluid dynamics method is used to investigate the effects of breaking wave loads on a 10-MW large-scale monopile offshore wind turbine under typical sea conditions in the eastern seas of China. Based on Fifth-Order Stokes wave theory a user-defined function is developed and used for wave numerical modelling, and a numerical wave tank with different bottom slopes is developed. Τhe effects of different types of breaking waves, such as spilling and plunging waves, on the wave run-up, pressure distribution and horizontal wave force of a large diameter monopile are investigated. Different numerical and analytical methods for calculating the wave breaking loads are used and their results are compared with the relevant results of the developed computational fluid dynamics model and their respective scopes of application are discussed. With an increase in wave height, the change in the hydrodynamic performance of breaking waves observed through the transition from plunging to spilling waves is explored. The intensity of interactions occurring between the breaking waves and the monopile foundation depends mainly on the form of wave breaking involved and its relationship to wave steepness is weak. Analytical methods for calculating the breaking wave loads are preservative especially for plunging breaking wave loads.